Vulture view - Sayre, April Pulley (Henry Holt, 2007)
"Turkey vultures soar on the balmy air, looking for their next stinky feast. These birds don't hunt--they like their food to be already dead. Vultures are part of nature's cleanup crew"--Inside front dust jacket.